STUDI LITERATUR TENTANG PENINGKATAN KEMAMPUAN LITERASI MATEMATIKA PADA MODEL PEMBELAJARAN PROBLEM BASED LEARNING - SURTIKA, WIJI; U.S, SUPARDI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2024)
This article presents the results of a literature study regarding improving students' mathematical literacy skills through the application of the Problem Based Learning (PBL) learning model. Mathematical literacy, as an important component in education, includes students' ability to understand, interpret and use mathematical concepts to solve problems in everyday life. The low mathematical literacy abilities of Indonesian students are of particular concern, because this ability has an important role in forming the critical and analytical thinking skills needed in the era of globalization. Therefore, there is a need for innovation in learning methods to improve students' mathematical literacy, one of which is through the PBL model. The PBL learning model is designed to encourage students to think independently, collaborate and be active in solving real problems that are relevant to the learning material. In this model, students are directly involved in the process of problem identification, analysis, and finding solutions, so that they can build a deep understanding and apply mathematical concepts contextually. The study results show that the implementation of structured PBL can increase students' mathematical literacy, critical thinking skills and independence. Therefore, PBL is recommended as an effective method in teaching mathematics, with training support for teachers for optimal implementation. ABSTRAKArtikel ini menyajikan hasil studi literatur mengenai peningkatan kemampuan literasi matematika siswa melalui penerapan model pembelajaran Problem Based Learning (PBL). Literasi matematika, sebagai salah satu komponen penting dalam pendidikan, mencakup kemampuan siswa dalam memahami, menafsirkan, dan menggunakan konsep matematika untuk memecahkan masalah dalam kehidupan sehari-hari. Rendahnya kemampuan literasi matematika siswa Indonesia menjadi perhatian khusus, karena kemampuan ini memiliki peran penting dalam membentuk keterampilan berpikir kritis dan analitis yang dibutuhkan di era globalisasi. Oleh karena itu, perlu adanya inovasi dalam metode pembelajaran untuk meningkatkan literasi matematika siswa, salah satunya melalui model PBL. Model pembelajaran PBL dirancang untuk mendorong siswa berpikir mandiri, berkolaborasi, dan aktif dalam memecahkan masalah nyata yang relevan dengan materi pembelajaran. Dalam model ini, siswa dilibatkan secara langsung dalam proses identifikasi masalah, analisis, dan pencarian solusi, sehingga mereka dapat membangun pemahaman yang mendalam dan menerapkan konsep matematika secara kontekstual. Hasil studi menunjukkan bahwa penerapan PBL yang terstruktur dapat meningkatkan literasi matematika, keterampilan berpikir kritis, dan kemandirian siswa. Oleh karena itu, PBL direkomendasikan sebagai metode efektif dalam pembelajaran matematika, dengan dukungan pelatihan bagi guru untuk penerapan yang optimal.